Role of Homeopathic Medicine in Respiratory Tract Infections (Advancements in Homeopathic Research, 2022)
Background: In general integrative medicine refers to all treatment protocol that is not part of the conventional healthcare regimes. The homeopathy system was developed in Europe at the end of the eighteenth century and used medicines obtained according to a well-defined procedure. This included mineral, herbal or animal substances etc. The techniques employed in preparing these medicines requires repeated dilution of the raw material in a hydro-alcoholic base or in other excipients, and preparing of the product into various grades Material and method: An observational study was conducted in the department of materia-medica of our institute for period of twelve months. Patients with chronic respiratory tract infection were taken as test samples. Age group of 18-60 were included in the test trial. A total of 547 patients were included in the study. 56% were male (306) and 44% were female (241). We included patients with respiratory tract infection of both upper or lower airways and the presence of a infection was considered when patients presented any ear, throat, airways or lungs infections, as well as sore throat, tonsillitis, laryngitis, sinusitis, runny nose, cough, common cold, etc. Results: Group A patients showed an initial relief in the symptoms of infection within 2 weeks of medication. Group B patients showed relief only from the 4 week of the symptoms. During the observation period of six months 87 patients of group A had a minimum of 1 episode of respiratory tract infection (32%); whereas, only 33 patients of group B patients (12%) showed any symptoms of respiratory infection. Conclusion: The efficacy of homeopathy is generally questionable, mainly due to the lack of a robust body of specific evidence. The respiratory tract infections usually have a direct impact on individual well-being.
Keywords: homeopathy; infections; respiratory